2002
DOI: 10.1034/j.1600-0706.2002.11989.x
|View full text |Cite
|
Sign up to set email alerts
|

The summer decline of the collared lemming,Dicrostonyx groenlandicus,in high arctic Greenland

Abstract: Gilg, O. 2002. The summer decline of the collared lemming, Dicrostonyx groenlandicus, in high arctic Greenland. -Oikos 99: 499-510.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 74 publications
(88 reference statements)
2
38
0
Order By: Relevance
“…In general, the amplitude of fluctuations is in the range of 20-200, with Siberia being well-known for its' high fluctuations in amplitude (Stenseth and Ims 1993). In eastern Greenland, cycle amplitude is estimated to be more than 100-fold (Gilg 2002).…”
Section: Extent Of Sea Ice and Fluctuations In Rodent Populationmentioning
confidence: 99%
“…In general, the amplitude of fluctuations is in the range of 20-200, with Siberia being well-known for its' high fluctuations in amplitude (Stenseth and Ims 1993). In eastern Greenland, cycle amplitude is estimated to be more than 100-fold (Gilg 2002).…”
Section: Extent Of Sea Ice and Fluctuations In Rodent Populationmentioning
confidence: 99%
“…Across most of its breeding range, it depends on cyclic lemming densities to breed (Andersson 1971(Andersson , 1976(Andersson , 1981Larson 2007;Maher 1970;Meltofte and Høye 2007), and there is a strong interaction between these two species (Gilg et al 2003). Along with a few other predators, the Long-tailed Skua regulates the Collared Lemming (Dicrostonyx groenlandicus) dynamics in Northeast Greenland (Gilg et al 2006;Schmidt et al 2008), especially during the peak phase of the lemming cycle when, along with the Snowy Owl (Nyctea scandiaca) and the Arctic Fox (Alopex lagopus), it is responsible for the rapid summer decline in lemming numbers (Gilg 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Most researchers agree that trophic interactions drive multi-annual high-amplitude cycles of northern rodent populations, although the relative importance of rodent-predator and plant-rodent interactions may vary between species and geographic areas (Jedrzejewski and Jedrzejewska, 1996;Korpima¨ki and Krebs, 1996;Turchin et al, 2000;Ergon et al, 2001;Hanski et al, 2001;Turchin and Batzli, 2001;Klemola et al, 2002b;Korpima¨ki et al, 2002Korpima¨ki et al, , 2005b. Even if there is no full consensus of the role of predation in the mechanism driving the cycles, radio telemetry studies have revealed that predation is the main mortality factor in the northern small rodent populations with multi-annual cycles Korpima¨ki, 1995, 1998;Steen, 1995;Banks et al, 2000;Gilg, 2002). Therefore predation has been evoked as a key factor in the models focusing on adaptive vs. non-adaptive behaviour in fluctuating vole populations (Ylo¨nen, 1994;Oksanen and Lundberg, 1995;Kaitala et al, 1997;Ruxton and Lima, 1997).…”
Section: Introductionmentioning
confidence: 97%